New progress in femtosecond laser-assisted cataract surgery - Yong-Mou Zhou (Press of International Journal of Ophthalmology (IJO PRESS), 2021)
In recent years, with the extensive development of phacoemulsification and the gradual application of femtosecond laser technology in the field of cataract surgery, femtosecond laser-assisted cataract surgery(FLACS)has become popular year by year, and has been recognized and promoted by more and more doctors. Femtosecond laser technology has high accuracy, automation and repeatability, so it is quite suitable for cataract surgery characterized by precision operation, it can be used in cataract surgery for corneal incision and limbal incision, anterior capsule incision, lens fragmentation and other key operations. FLACS has broad application prospects and can greatly improve the predictability and safety of surgery. The emergence of FLACS is one of the most important developments in modern cataract surgery. With the continuous development of FLACS, cataract surgery will usher in new technological innovations. However, FLACS are relatively new, and longer term, more comprehensive data are still needed to better demonstrate their effectiveness in the future. We review the current research progress of FLACS.